2022
DOI: 10.3389/fimmu.2022.856966
|View full text |Cite
|
Sign up to set email alerts
|

BET Protein Inhibition Regulates Macrophage Chromatin Accessibility and Microbiota-Dependent Colitis

Abstract: IntroductionIn colitis, macrophage functionality is altered compared to normal homeostatic conditions. Loss of IL-10 signaling results in an inappropriate chronic inflammatory response to bacterial stimulation. It remains unknown if inhibition of bromodomain and extra-terminal domain (BET) proteins alters usage of DNA regulatory elements responsible for driving inflammatory gene expression. We determined if the BET inhibitor, (+)-JQ1, could suppress inflammatory activation of macrophages in Il10-/- mice.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…For example, the treatment of JQ1 inhibited the inflammatory gene transcription associated with LPS stimulation and prevented LPS‐induced sepsis (Belkina et al, 2013; Nicodeme et al, 2010). Hoffner O'Connor et al (2022) showed that JQ1 suppressed LPS‐induced changes in chromatin at distal regulatory elements associated with inflammatory genes, particularly in regions that contain motifs for AP‐1 and IRF transcription factors, and attenuated the onset of microbiota‐induced colitis. In inflammatory bone disease, both JQ1 and I‐BET 151 are pan‐bromodomain inhibitors, and can prevent pathological bone resorption in experimental arthritis (Park‐Min et al, 2014), oestrogen‐related osteoporosis (Baud'huin et al, 2017; Park‐Min et al, 2014) and alveolar bone loss (Meng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the treatment of JQ1 inhibited the inflammatory gene transcription associated with LPS stimulation and prevented LPS‐induced sepsis (Belkina et al, 2013; Nicodeme et al, 2010). Hoffner O'Connor et al (2022) showed that JQ1 suppressed LPS‐induced changes in chromatin at distal regulatory elements associated with inflammatory genes, particularly in regions that contain motifs for AP‐1 and IRF transcription factors, and attenuated the onset of microbiota‐induced colitis. In inflammatory bone disease, both JQ1 and I‐BET 151 are pan‐bromodomain inhibitors, and can prevent pathological bone resorption in experimental arthritis (Park‐Min et al, 2014), oestrogen‐related osteoporosis (Baud'huin et al, 2017; Park‐Min et al, 2014) and alveolar bone loss (Meng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In haematoxylin and eosin staining (Figure6c), compared with DMSO group, RVX-208 treatment appeared to result in less epithelium hyperplasia and less immune cell infiltration.4 | DISCUSSIONIn recent years, BET inhibitors have emerged as promising candidates for treating inflammatory diseases. For example, the treatment of JQ1 inhibited the inflammatory gene transcription associated with LPS stimulation and prevented LPS-induced sepsis(Belkina et al, 2013;Nicodeme et al, 2010) Hoffner O'Connor et al (2022). showed that JQ1 suppressed LPS-induced changes in chromatin at distal regulatory elements associated with inflammatory genes, particularly in regions U R E 3 RVX-208 inhibited osteoclast differentiation.…”
mentioning
confidence: 99%
“…Because inhibitors of BET proteins were demonstrated to efficiently attenuate several LPS-evoked changes [2,32], the second goal of this study was to analyse the impact of JQ1, an inhibitor of BET proteins, on LPS-changed expression of AD-GRF genes in the hippocampus during systemic inflammation. In mice, JQ1 is well tolerated even after chronic treatment, and it efficiently enters the brain (AUC brain /AUC plasma = 98%) [43,45,48].…”
Section: Discussionmentioning
confidence: 99%
“…This emerges as a potent approach to inhibit inflammation cascades because it prevents the transcription initiation of inflammatory genes. Nicodeme et al (2010) successfully synthesized a compound (GSK525762A, IBET762) that mimicked acetylated histones and disrupted chromatin complexes responsible for the expression of key inflammatory genes in activated macrophages, while also conferring protection against LPS-induced endotoxic shock and bacteria-induced JQ1, a well-studied pan-BET inhibitor, suppressed the activation of a specific subset of LPS-inducible genes that encode cytokines, chemokines, and transcription factors involved in inflammatory response (Belkina et al, 2013;Hoffner O'Connor et al, 2022). The presence of JQ1 disassociates BET proteins from the promoters and super-enhancers of pro-inflammatory genes (Belkina et al, 2013;Hoffner O'Connor et al, 2022;Krishna et al, 2021).…”
Section: Suppression Of Inflammation By Targeting Bromodomainsmentioning
confidence: 99%